2013
DOI: 10.1073/pnas.1315215111
|View full text |Cite
|
Sign up to set email alerts
|

Role of ocean heat transport in climates of tidally locked exoplanets around M dwarf stars

Abstract: The distinctive feature of tidally locked exoplanets is the very uneven heating by stellar radiation between the dayside and nightside. Previous work has focused on the role of atmospheric heat transport in preventing atmospheric collapse on the nightside for terrestrial exoplanets in the habitable zone around M dwarfs. In the present paper, we carry out simulations with a fully coupled atmosphere-ocean general circulation model to investigate the role of ocean heat transport in climate states of tidally locke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
82
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 32 publications
(31 reference statements)
7
82
0
1
Order By: Relevance
“…But subsequent investigations with simplified climate models (Haberle et al 1996) and general circulation models (GCMs) (Joshi et al 1997;Joshi 2003;Merlis & Scheider 2010;Edson et al 2011;Showman et al 2010Showman et al , 2013Leconte et al 2013;Yang et al 2013Cullum et al 2014;Hu & Yang 2014;Carone et al 2014Carone et al , 2015Carone et al , 2016Wordsworth 2015;Way et al 2016;Kopparapu et al 2016Kopparapu et al , 2017Noda et al 2017;Fujii et al 2017) have demonstrated that energy transport from the day to night hemisphere is generally sufficient to avoid atmospheric collapse across a wide range of atmospheric compositions and rotation periods.…”
Section: Introductionmentioning
confidence: 99%
“…But subsequent investigations with simplified climate models (Haberle et al 1996) and general circulation models (GCMs) (Joshi et al 1997;Joshi 2003;Merlis & Scheider 2010;Edson et al 2011;Showman et al 2010Showman et al , 2013Leconte et al 2013;Yang et al 2013Cullum et al 2014;Hu & Yang 2014;Carone et al 2014Carone et al , 2015Carone et al , 2016Wordsworth 2015;Way et al 2016;Kopparapu et al 2016Kopparapu et al , 2017Noda et al 2017;Fujii et al 2017) have demonstrated that energy transport from the day to night hemisphere is generally sufficient to avoid atmospheric collapse across a wide range of atmospheric compositions and rotation periods.…”
Section: Introductionmentioning
confidence: 99%
“…The zonal oceanic heat transport caused by the dynamical ocean circulation was found to reduce the seaice thickness on the nightside to 5 m (Hu and Yang 2014) compared to a sea-ice thickness of 100 m in the uncoupled simulations (Pierrehumbert 2010). However, their synchronous rotation period is 36.7 Earth-days, while ours is 365 Earth-days.…”
Section: Discussionmentioning
confidence: 70%
“…However, their synchronous rotation period is 36.7 Earth-days, while ours is 365 Earth-days. We therefore expect a smaller day-tonight oceanic heat transport in our case because the geostrophic balance breaks down at longer rotation period, and thus the ocean currents won't be necessarily zonal as in Hu and Yang (2014). Nonetheless, we expect that ocean circulation would reduce the temperature gradients and the sea-ice cover for non-synchronous rotations.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…There are many studies describing simulations of exoplanetary atmospheric circulations and climate (4), but most incorporate either no ocean (5-7) or a heavily simplified slab ocean (8)(9)(10)(11)(12). Only recently have studies considered a dynamical ocean (13)(14)(15)(16), and even in these studies, the ocean is consistently assumed to have similar properties to the oceans on Earth. Such an assumption may prove to be an oversimplification.…”
mentioning
confidence: 99%